Inhibitory Effects of Daiokanzoto (Da-Huang-Gan-Cao-Tang) on P-Glycoprotein. (27th August 2012) - Watanabe, Yuka; Ikarashi, Nobutomo; Satoh, Toshiyuki; Ito, Kiyomi; Ochiai, Wataru; Sugiyama, Kiyoshi
Abstract : We have studied the effects of various Kampo medicines on P-glycoprotein (P-gp), a drug transporter, in vitro . The present study focused on Daiokanzoto (Da-Huang-Gan-Cao-Tang), which shows the most potent inhibitory effects on P-gp among the 50 Kampo medicines studied, and investigated the P-gp inhibitory effects of Daiokanzoto herbal ingredients (rhubarb and licorice root) and their components by an ATPase assay using human P-gp membrane. Both rhubarb and licorice root significantly inhibited ATPase activity, and the effects of rhubarb were more potent than those of licorice root. The content of rhubarb in Daiokanzoto is double that in licorice root, and the inhibition patterns of Daiokanzoto and rhubarb involve both competitive and noncompetitive inhibition, suggesting that the inhibitory effects of Daiokanzoto are mainly due to rhubarb. Concerning the components of rhubarb, concentration-dependent inhibitory effects were observed for (−)-catechin gallate, (−)-epicatechin gallate, and (−)-epigallocatechin gallate. In conclusion, rhubarb may cause changes in the drug dispositions of P-gp substrates through the inhibition of P-gp. It appears that attention should be given to the interactions between these drugs and Kampo medicines containing rhubarb as an herbal ingredient.